2001
DOI: 10.1128/aem.67.1.155-161.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Workers to Airborne Microorganisms in Open-Air Swine Houses

Abstract: This study quantified the levels of airborne microorganisms in six swine farms with more than 10,000 pigs in subtropical Taiwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 28 publications
(47 reference statements)
11
105
1
Order By: Relevance
“…In contrast, previous CAFO bioaerosol studies based on culture counts concluded that fungi contributed a sizable portion of the overall observed (via culture) airborne ecology (Hanhela et al 1995;Chang et al 2001;Adhikari et al 2004a,b;Jo and Kang 2005;Chi and Li 2005;Lee et al 2006;Kim et al 2008). This conclusion based on culture, however, is not supported by our results.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In contrast, previous CAFO bioaerosol studies based on culture counts concluded that fungi contributed a sizable portion of the overall observed (via culture) airborne ecology (Hanhela et al 1995;Chang et al 2001;Adhikari et al 2004a,b;Jo and Kang 2005;Chi and Li 2005;Lee et al 2006;Kim et al 2008). This conclusion based on culture, however, is not supported by our results.…”
Section: Discussionmentioning
confidence: 54%
“…Until very recently, CAFO aerobiology has been characterized mainly with culture-based techniques that emphasize species that grow best at moderate temperature under oxic conditions (Cormier et al 1990;Crook et al 1991;Chang et al 2001;Predicala et al 2002;Jo and Kang 2005;Kim et al 2008). Our study sidestepped these constraints by use of cultureindependent technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other parts of swine houses (e.g., nurseries with slatted floors, where waste is regularly cleaned away) had significantly lower amounts of total culturable and Gramnegative bacteria. 6 Moreover, the genus Stenotrophomonas has been identified in samples of compost of swine manure. 24 Hence, swine feces seem to be a significant source of airborne Gram-negative bacteria in swine houses.…”
Section: Discussionmentioning
confidence: 99%
“…These values were adopted from a study that was previously carried out in Taiwan. 6 The air-exchange rate (ACH) was 1 hr Ϫ1 (Ϯ3%), which is typical of buildings with mild ventilation. Such setup yielded an airflow of 0.01 m/sec above the sample.…”
Section: Controlled Facilitymentioning
confidence: 99%